Is air transport sustainable in remote regions? A socio-environmental perspective - André Oliveira; Pedro Pimentel; Gualter Couto (Journal of Applied Economics, 2025)
Air transport is crucial for ensuring population mobility owing to time travel savings, especially in remote regions. Despite its benefits, air transport is still one of the most polluting industries worldwide. Under the European Green Deal, sustainable transport needs to be enhanced to promote sustainable economic development, revealing the need for better decision-making tools. Nonetheless, limited research presents valuation frameworks under uncertainty and socio-environmental impacts simultaneously. Using a real options analysis and utility theory, a valuation framework is developed to assess the economic and socio-environmental impacts of air transport under Public Service Obligations. The results for the Azores case, a nine-island archipelago in Portugal, show a positive impact on social welfare. This study contributes to the literature by developing a valuation framework suitable for assessing sustainable transport networks and by presenting a case study with real data.